Methionine sulfoxide reductase (MsrA) is a regulator of antioxidant defense and lifespan in mammals - Moskovitz, Jackob (The National Academy of Sciences, 2001)
Oxidation of proteins by reactive oxygen species is associated with aging, oxidative stress, and many diseases. Although free and protein-bound methionine residues are particularly sensitive to oxidation to methionine sulfoxide derivatives, these oxidations are readily repaired by the action of methionine sulfoxide reductase (MsrA). To gain a better understanding of the biological roles of MsrA in metabolism, we have created a strain of mouse that lacks the MsrA gene. Compared with the wild type, this mutant: (i) exhibits enhanced sensitivity to oxidative stress (exposure to 100% oxygen); (ii) has a shorter lifespan under both normal and hyperoxic conditions; (iii) develops an atypical (tip-toe) walking pattern after 6 months of age; (iv) accumulates higher tissue levels of oxidized protein (carbonyl derivatives) under oxidative stress; and (v) is less able to up-regulate expression of thioredoxin reductase under oxidative stress. It thus seems that MsrA may play an important role in aging and neurological disorders.